Prognostic Implications of Sex in Patients With Heart Failure With Mildly Reduced Ejection Fraction: Results From a Large‐Scaled Registry - Marielen Reinhardt; Michael Behnes; Kathrin Weidner; Mohammad Abumayyaleh; Felix Lau; Alexander Schmitt; Noah Abel; Daniel Duerschmied; Christel Weiß; Muharrem Akin; Ibrahim Akin; Tobias Schupp (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The study investigates the prognostic impact of sex and sex‐related differences in patients hospitalized with heart failure with mildly reduced ejection fraction (HFmrEF). More data regarding the characterization of patients and their outcomes in the presence of HFmrEF are needed. Methods and Results Consecutive patients hospitalized with HFmrEF (ie, left ventricular ejection fraction 41%–49% and signs or symptoms of HF) were retrospectively included at one institution from 2016 to 2022. Female patients were compared with male patients with regard to the primary end point of all‐cause mortality at 30 months (median follow‐up). Statistical analyses comprised Kaplan–Meier, multivariable Cox proportional regression analyses and propensity score matching. From a total of 2184 patients hospitalized with HFmrEF, 64.6% were male. Female patients with HFmrEF were older than male patients (median age 78 versus 73 years; P=0.001) and had lower rates of ischemic cardiomyopathy (46.6% versus 63.6%; P=0.001). Within the entire study cohort, sex was not associated with the risk of all‐cause mortality (hazard ratio [HR], 0.931 [95% CI, 0.797–1.088]; P=0.372). However, male sex was associated with a lower risk of HF‐related rehospitalization at 30 months (HR, 0.761 [95% CI, 0.600–0.966]; P=0.026), which was confirmed after multivariable adjustment (HR, 0.759 [95% CI, 0.592–0.973]; P=0.029) and propensity score matching (HR, 0.722 [95% CI, 0.539–0.967]; P=0.029). Conclusion Although almost two thirds of patients hospitalized with HFmrEF were male, sex was no predictor for the risk of all‐cause mortality at 30 months. However, female sex was associated with a higher risk of HF‐related rehospitalization. Registration URL: https://clinicaltrials.gov; Unique identifier: NCT05603390.